1998
DOI: 10.1016/s0002-9440(10)65583-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Vascular Endothelial Growth Factor C Receptor VEGFR-3 in Lymphatic Endothelium of the Skin and in Vascular Tumors

Abstract: It is difficult to identify lymph vessels in tissue sections by histochemical staining, and thus a specific marker for lymphatic endothelial cells would be more practical in histopathological diagnostics. Here we have applied a specific antigenic marker for lymphatic endothelial cells in the human skin, the vascular endothelial growth factor receptor-3 (VEGFR-3), and show that it identifies a distinct vessel population both in fetal and adult skin, which has properties of lymphatic vessels. The expression of V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
144
0
3

Year Published

1999
1999
2004
2004

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 182 publications
(154 citation statements)
references
References 31 publications
7
144
0
3
Order By: Relevance
“…VEGFR-3 has been found in most endothelia during embryogenesis. Later in development, it becomes restricted to lymphatic endothelium in most tissue (24,25). It has also been found to be upregulated in the endothelial cells of tumor neovascularization (26) and is consistently expressed in lymphangiomas (25), Kaposi's sarcoma (24), and in hemangiomas and angiosarcomas (27).…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR-3 has been found in most endothelia during embryogenesis. Later in development, it becomes restricted to lymphatic endothelium in most tissue (24,25). It has also been found to be upregulated in the endothelial cells of tumor neovascularization (26) and is consistently expressed in lymphangiomas (25), Kaposi's sarcoma (24), and in hemangiomas and angiosarcomas (27).…”
Section: Discussionmentioning
confidence: 99%
“…The major site of expression in the adult organism is in the lymphatics, and it has been employed as a marker for lymphatic vessels in normal and pathological tissue samples 32 and has been used to demonstrate an apparent lymphatic origin of Kaposi's sarcoma cells. 15 VEGFR-3 is one of several markers for lymphatic endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that the VEGFR-3 may be useful in the differentiation of lymphatic vessels from blood vessels. 15 The usefulness of a combined assessment using both factor VIII-related antigen and VEGFR-3 should be investigated further. BVI, which predominantly includes capillary vessel invasion, appears to be a significant predictor of ovarian metastasis and patient survival when determined separately from LVI on HE stained sections.…”
Section: Discussionmentioning
confidence: 99%